Karakterisasi Petrografi dan Klasifikasi Litologi Batuan pada Daerah Umpam dan Sekitarnya, Kecamatan Lengkiti, Kabupaten Ogan Komering Ulu, Sumatera Selatan - Khatulistiwa, Bening Alya; Idarwati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Umpam area and its surroundings, Lengkiti District, Ogan Komering Ulu Regency, South Sumatra, are located within the South Sumatra Basin and exhibit complex lithological variations. This study aimed to characterize rock types petrographically and to establish lithological classifications as a basis for more accurate rock nomenclature. The research methods included field observations, sample collection, thin section preparation, and petrographic analysis using a polarizing microscope under plane-polarized light (PPL) and cross-polarized light (XPL). The petrographic analysis of 12 samples revealed lithologies consisting of calcareous pelite (slate) and metacarbonate rock (phyllite) within the Tarap Formation (PCt); chert within the Situlanglang Member (Kjgs); chert and andesite within the Insu Member of the Garba Formation (KJgv); lithic tuff, andesite, and basalt within the Kikim Formation (Tpok); ferruginous lithic wacke within the Talang Akar Formation (Tomt); and wackestone limestone within the Baturaja Formation (Tmb). The Gumai Formation (Tmg) is also characterized by calcareous mudrock and wackestone. Overall, the study area is composed of metamorphic, igneous, pyroclastic, and sedimentary rocks, reflecting the diversity of geological processes that have occurred in the region.